Autism Spectrum Disorders as Seen by a Clinical Psychologist: Case Report - Eva Horáčková (Listy klinicke logopedie)
Autism Spectrum Disorders are pervasive developmental disorders. This means that they influence almost all areas of early development. Parents can see differences mainly in the social area. Children with ASD do not share activities, do not communicate their needs and wishes. At the age of 18 months, parents fill in the M-CHAT-R screening, which is sensitive to possible neurodevelopmental problems. A paediatrician can send the child to specialists in ASD diagnosis - clinical psychologist, child psychiatrist, neurologist and clinical speech therapist. In this article, we introduce you to a case study with differential diagnoses, showing the differences between Autism Spectrum Disorders and other developmental diseases (especially specific developmental disorders of speech and language). The focus is on the determination of the autistic symptoms level. This is one of the typical differential diagnoses we carry out at LOGO Clinic.